Computational mathematics (Narosa Publishing House, 2005)
Computational Mathematics presents a real life system, which is always challenging for scientists and engineers. Concerned with the design and control of continuum systems and processes, it emphasizes the solution of a general class of inverse/design problems and presents methodologies for dynamic coupling between experiments and computation. The book reviews computational design models that can be used to point to the field variables that are best to measure as well as the most effective control mechanisms having major impact on the physical phenomena one is interested to control. The field of computational mathematics also concerns algorithmic developmental approach for mathematically driven data mining and reduced-order modeling of continuum systems.